Metronomic palliative chemotherapy in maxillary sinus tumor - Patil, Vijay M.; Noronh, Vanita; Joshi, Amit; Karpe, Ashay; Talreja, Vikas; Chandrasekharan, Arun; Dhumal, Sachin; Prabhash, Kumar (South Asian Journal of Cancer, 2016)
Background: Metronomic chemotherapy consisting of methotrexate and celecoxib recently has shown promising results in multiple studies in head and neck cancers. However, these studies have not included patients with maxillary sinus primaries. Hence, the role of palliative metronomic chemotherapy in patients with maxillary sinus carcinoma that is not amenable to radical therapy is unknown. Methods: This was a retrospective analysis of carcinoma maxillary sinus patients who received palliative metronomic chemotherapy between August 2011 and August 2014. The demographic details, symptomatology, previous treatment details, indication for palliative chemotherapy, response to therapy, and overall survival (OS) details were extracted. SPSS version 16 was used for analysis. Descriptive statistics have been performed. Survival analysis was done by Kaplan-Meier method. Results: Five patients had received metronomic chemotherapy. The median age was 60 years (range 37-64 years). The proportion of patients surviving at 6 months, 12 months, and 18 months were 40%, 40%, and 20%, respectively. The estimated median OS was 126 days (95% confidence interval 0-299.9 days). The estimated median survival in patients with an event-free period after the last therapy of <6 months was 45 days, whereas it was 409 days in patients with an event-free period postlast therapy above 6 months (P = 0.063). Conclusion: Metronomic chemotherapy in carcinoma maxillary sinus holds promise. It has activity similar to that seen in head and neck cancers and needs to be evaluated further in a larger cohort of patients.
Keywords: Chemotherapy; head and neck cancer; maxilla; metronomic; palliative